Un entretien avec Diane Labrosse - Cornell, Andrea-Jane (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This interview with Diane Labrosse was conducted in December 2004 in the offices of Production SuperMusique within the framework of Dr. Andra McCartney's In and Out Of the Sound Studio project. Andrea Jane Cornell asked Labrosse about the experiences that brought her to choose sound as a medium for her artistic expression, and the methods that she employs to create sound.

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.